The Use of Androgen Deprivation Therapy in Combination With Radiation for Localized Prostate Cancer - Anderson, Eric M.; McBride, Sean M. (Frontiers in Urology, 2022)
Context The combined use of androgen deprivation therapy (ADT) and radiotherapy in the initial treatment of intermediate- and high-risk prostate cancer is well established. Objectives This study aims to review level 1 evidence and post-hoc analyses from prospective studies to determine the benefit of the addition of ADT to curative radiotherapy in prostate cancer and provide suggestions for future combinatorial trials in localized disease. Evidence Acquisition We used PubMed with the terms “radiation”, “ADT”, and “prostate” to identify randomized controlled trials that compared curative therapy alone to curative therapy with androgen deprivation therapy conducted from 1980 to the present extracted by the senior author. For critical questions for which randomized data were unavailable, we used studies selected by the senior author that relied on post-hoc analyses from prospective randomized trials in an attempt to provide substantive answers. Evidence Synthesis There is strong and unequivocal evidence that variable-length ADT in combination with curative dose radiotherapy improves biochemical recurrence-free survival, cause-specific survival (CSS), and overall survival in intermediate- and high-risk prostate cancer. Evidence Summary ADT should be a component of treatment for most men with unfavorable intermediate- and high-risk prostate cancer receiving curative dose radiotherapy